Development of Indonesian History-Based Learning Media Videoscribe Material on the Islamic Kingdom in Java for Class X at SMA Negeri 3 Salatiga - Munawar, Ainun; Suryadi, Andy (Indonesian Journal of History Education, 2022)
The purpose of this research is (1) To analyze the media needs of Indonesian history, (2) to know the development of Indonesian history learning media-based videoscribe Demak kingdom material, (3) to know the media feasibility of Indonesian history study-based Videoscribe material of Islamic kingdom in Java sub material of Demak Kingdom given validation results conducted by material expert and media expert as well as teacher and student assessment. The method used in this research is research and development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of this research show (1) That the learning media used by the history teacher of SMA Negeri 3 Salatiga Only used PowerPoint, picture video taken from the Internet, and a monotonous learning model resulted in subjects. Indonesia's history has become dull and less attractive, requiring more interesting learning media. (2) The development of Indonesian history Learning media Demak Kingdom material is made using the Sparkol Videoscribe software, which is based on media scripts and narratives (3) Based on the feasibility rate of material expert validation, media experts and learning experts respectively with a percentage yield of 88.55%, 94.65%, and 93.75%. And student assessment results of 86.5%. Thus, this media should be used to study Islamic kingdom material in Java, the Demak Kingdom's sub-material.